Working Environment and Staff Performance In Local Government: A Case Study of Rubanda District Local Government. - Musiimenta, Dan (Kabale University, 2024)
The study considered the impact of working environment and staff performance in local government: A case study of Rubanda District Local Government. The study was guided by the work environment factors that influence staff performance in the Rubanda district, the effect of the working environment on employee performance in the Rubanda district, and the factors that affect employee performance in the Rubanda district. The study used a descriptive research design that aimed at generating information after the incident had occurred; the Qualitative approach included the use of interviews. Data was collected using a questionnaire and interview guide, and simple random and purposive sampling methods were used. Both qualitative and quantitative methodologies were used to analyze data as a sample size of 50 respondents was used. The study revealed the work environment factors that influence staff performance in the Rubanda district and these include psychological work, temperature factor, sound factor, space factor, physical work environment, and air factor. The study revealed the effect of working environment on employee performance and these include; employees who are engaged will improve their performance, inadequate efficiency and dependency, work environment is the physical location and the environment of the workplace, absenteeism, early retirement, turnover, low workers performance, committed workers who are greatly motivated by good working atmosphere, un¬conduci ve work environment creates a feeling of un-fulfillment. Lastly, that the study of the factors that affect employee performance; experience at work, organizational Commitment, goals and expectations of an employee, organizational Culture, and motivation. The study recommended that to promote a good working environment and good performance of employees, employee motivation, experience at work, organizational culture, organizational commitment, goals, and expectations of an employee, tools, and equipment should be considered.